GROUP COUNSELING AS SELF-ESTEEM AND MOTIVATION INTERVENTION FOR TRUANCY PROBLEMATIC STUDENTS: A MALAYSIAN CASE STUDY - Tharishini Mana Mohan; Abu Yazid Abu Bakar (Universitas PGRI Madiun, 2021)
The study aims to determine whether the students who presented group counseling for lower trigonometry differed from those in the comparison group. The experimental research plan was used. The number of participants who participated in the study selected several students. Study results indicated that individuals in the treatment group could reduce their worldly behavior; The number of students in the actual practice of basic self-management goals increases compared to students with self-capability goals triples among students during the counselling sessions. However, the recommendations made with this study included a greater need for additional counseling on how to change school behavior rather than using physical punishment.